Predicting Reduced Tinnitus Burden After Cochlear Implantation in Adults. Issue 2 (February 2020) - Dixon, Peter R.; Crowson, Matthew; Shipp, David; Smilsky, Kari; Lin, Vincent Y.; Le, Trung; Chen, Joseph M.
Abstract : Objective: Explore patient characteristics associated with tinnitus improvement after cochlear implantation. Study Design: Retrospective cohort. Setting: Tertiary referral. Patients: Adults with bilateral severe-to-profound hearing loss and tinnitus. Interventions: Unilateral cochlear implantation. Results: From 1996 to 2018, 358 patients endorsed pre-implant tinnitus and had ascertainable tinnitus status at 1-year. Clinically significant improvement in Tinnitus Handicap Inventory (THI) (reduction by at least 7-points) was observed in 262 (73.2%) patients, of whom 155 (59.2%) reported complete resolution. Of the 24 characteristics explored, four were identified as independent predictors of improved tinnitus in logistic regression models. In a multivariable model including identified independent predictors, each 10-percentage point increase in baseline hearing in noise test was associated with an 14% reduction in odds of tinnitus resolution or clinically significant improvement (odds ratio [OR] 0.86, 95% confidence limits [CL] 0.77, 0.96) and preoperative use of a hearing aid in the contralateral ear was associated with a 72% reduction (OR 0.28; 95% CL 0.11, 0.73). Each 10-point increase in baseline Hearing Handicap Inventory for Adults (HHI) score was associated with a 28% increase in odds of tinnitus improvement (OR 1.28; 95% CL 1.07, 1.54). Higher baseline burden of tinnitus was associated with higher odds of tinnitus improvement (OR 1.21 per 10-point THI increase, 95% CL 1.04, 1.40). Conclusions: Worse residual hearing and higher baseline hearing and tinnitus handicap are associated with higher odds of tinnitus improvement. Expectations of patients seeking reduced tinnitus burden following cochlear implantation should be managed by counselling regarding odds of tinnitus improvement compared to those with similar residual hearing and tinnitus burden.